Mixed adenoneuroendocrine carcinoma of the gallbladder, histopathological features - Shweta Azad; Deepti Shukla; Ankur Garg; Sanjay Singh Negi; Veena Malhotra (Wolters Kluwer Medknow Publications, 2015)
An unusual case of mixed adenoneuroendocrine carcinoma is described which posed a diagnostic challenge in view of neuroendocrine component mimicking signet ring cells of adenocarcinoma. Diagnostic criteria for these mixed tumors, their histogenesis and treatment modalities are highlighted.